A Silurian armoured aplacophoran and implications for molluscan phylogeny. - Sutton, MD; Briggs, D; Siveter, D; Siveter, D; Sigwart, J (2012)
The Mollusca is one of the most diverse, important and well-studied invertebrate phyla; however, relationships among major molluscan taxa have long been a subject of controversy. In particular, the position of the shell-less vermiform Aplacophora and its relationship to the better-known Polyplacophora (chitons) have been problematic: Aplacophora has been treated as a paraphyletic or monophyletic group at the base of the Mollusca, proximate to other derived clades such as Cephalopoda, or as sister group to the Polyplacophora, forming the clade Aculifera. Resolution of this debate is required to allow the evolutionary origins of Mollusca to be reconstructed with confidence. Recent fossil finds support the Aculifera hypothesis, demonstrating that the Palaeozoic-era palaeoloricate 'chitons' included taxa combining certain polyplacophoran and aplacophoran characteristics. However, fossils combining an unambiguously aplacophoran-like body with chiton-like valves have remained elusive. Here we describe such a fossil, Kulindroplax perissokomos gen. et sp. nov., from the Herefordshire Lagerstätte (about 425 million years bp), a Silurian deposit preserving a marine biota in unusual three-dimensional detail. The specimen is reconstructed three-dimensionally through physical-optical tomography. Phylogenetic analysis indicates that this and many other palaeoloricate chitons are crown-group aplacophorans.